If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18x = 8x + -24 Reorder the terms: -18x = -24 + 8x Solving -18x = -24 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -18x + -8x = -24 + 8x + -8x Combine like terms: -18x + -8x = -26x -26x = -24 + 8x + -8x Combine like terms: 8x + -8x = 0 -26x = -24 + 0 -26x = -24 Divide each side by '-26'. x = 0.9230769231 Simplifying x = 0.9230769231
| (3-3y^2)-2y(3-3y)+3y^2=27 | | (3-3y^2)-2y(3-3y^2)+3y^2=27 | | 6x+3x=4 | | 4y^2-5x-16y+21=0 | | x^4-2x^3-5x^2-4x+4=0equation | | 5(x+3)=4(2-4x) | | X^2-y^2=105 | | -8x+4x=-96+12 | | 20x+28=21-15x | | 0=x^2-5x+7 | | 100=5x-(5x-x)(5x-x) | | 4x^2+8=3x+15 | | 4x+1=20x | | 3xz-3xy=0 | | 10squared=5x-(5x-x)(5x-x) | | 0.05xa=5 | | 8d-4=12-14 | | 5sinx-12cosx-9=0 | | 7(p-8)=8p+35 | | (-1)a=-a | | R=H+4*20 | | 10+2x^3=7 | | 4*4x+7-5x=8+(-5)(5x-6x)+23 | | 3x+3(-2x)=x-3 | | 3(m+5)= | | 7(2x-1)=4x+3 | | g(x)=-3x^2+30x-77 | | 114=19y | | p^2(p^2-4)=3p^2+-8 | | 3*4x=35+5x | | 9w=5670 | | p^2(p^2-4)=3p^2-8 |